The Exposure of Microfinance Institutions to Financial Risk - Thomas Gietzen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This study examines the exposure of microfinance institutions to liquidity, interest rate and foreign exchange (FX) risk. It builds on a manually collected set of data on the maturity structure of assets and liabilities of the 309 largest microfinance institutions (out of which 112 actually report the maturity structure). The data suggests that, on average, microfinance institutions in the sample face virtually no liquidity risk and that exposure to FX risk is lower than generally assumed. Linking risk exposure to institutional characteristics, I find that legal status and regional affiliation are correlated to risk exposure while regulatory quality is not.
Keywords: G21; G32; O16; 330